Elections in Britain - Leonard, D. author. aut Link
X, 281 p.
Keywords: How do British elections work? What about local elections and by-elections? How are candidates chosen? What has been the impact of changes introduced by the present government? How can an ordinary voter play his or her part? And why do so few people vote these days? Dick Leonard, a political journalist and former MP, and Roger Mortimore, an opinion pollster, cover all aspects of British elections in this updated edition of the standard work, including comprehensive tables of statistics and results.